DESCRIPTION OF ACID-RESISTANT BACTERIA EXAMINATION IN PATIENT FOLLOW UP TUBERCULOSIS IN THE WORKING AREA OF BLUD PUSKESMAS PERUMNAS, LUBUKLINGGAU BARAT I - Widiawati, Widiawati; Karwiti, Witi; Garini, Ardiya; Harianja, Sri Hartini (Journal of Medical Laboratory and Science, 2021)
Background: Tuberculosis (TB) is an infectious disease caused by stem-shaped bacteria known as Mycobacterium tuberculosis. Transmission through saliva media or phlegm sufferers containing pulmonary tuberculosis basil. Pulmonary TB is a major public health problem with the number 3rd most in the world after China and India, with about 10% of the total number of people with pulmonary TB in the world. There are an estimated 539,000 new cases and 101,000 deaths each year. The number of pulmonary TB events in Indonesia characterized by the presence of positive acid-resistant bacteria in patients is 110 per 100,000 inhabitants. The purpose of the study to find out the description of the examination of acid-resistant bacteria in people with Pulmonary TB in the working area of BLUD Puskesmas Perumnas Lubuklinggau Barat Lubuklinggau District in 2018. Method: This study is descriptive research with cross sectional study design with axial. sampling method. Result: After conducting research on lung TB follow-up patients as many as 22 people who were originally positive for Pulmonary TB in the working area of BLUD Puskesmas District Perumnas Lubuklinggau Barat city I in 2018 obtained the results of research as many as 22 people (100 %) BTA test results were negative, based on education obtained by 9 people (40.9%) universities with negative BTA results and 13 people (59.1%) low education negative BTA results. Based on knowledge obtained by 22 people (100%) have good knowledge with negative BTA results. Based on the compliance of taking drugs obtained 22 people (100%) have adherence to ingesting the drug in accordance with negative BTA results. Based on the attitude of health workers obtained 22 people (100%) stated the attitude of health workers have a good attitude. Conclusion: BTA examination in all TB patients followed up with negative results.